KREATIVITAS SEBAGAI MEDIATOR PENGARUH PEMBERDAYAAN PADA KINERJA PENGELOLA LEMBAGA PERKREDITAN DESA (LPD) DI KABUPATEN GIANYAR - Sintaasih, Desak Ketut; Indrawati, Ayu Desi; Satrya, I Gst. Bgs Honor (JUIMA : JURNAL ILMU MANAJEMEN, 2019)
This study aims to analyze the effect of empowerment on the creativity and performance of managers of Village Credit Institutions (LPD) in Gianyar Regency and examine the role of creativity as mediating the inï€‚uence of empowerment on performance. This research was tested on 120 LPD managers spread across Payangan, Gianyar, and Sukawati Districts. The analysis technique used is path analysis. The results showed that empowerment and creativity had a positive and signiï€cant direct inï€‚uence on the performance of LPD managers. Research also shows that empowerment has an indirect effect on manager's performance through creativity, so that it can be said that the creativity variable has a role as a mediating variable.